Big healthcare data sets: circulation of data and new forms of belonging (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Digitalization of healthcare pursues general interest, aimed at encouraging medical care and improving the quality standards of healthcare systems, enhancing the predictive nature of medicine. These objectives are achievable above all thanks to the large-scale of health data processing, the discipline of which, however, being modeled on the collection of individual data, does not offer secure protection either to informative self-determination or to the privacy of users-patients. In this context, the reconstructive proposal of healthcare data sets as resources under shared management makes it possible to recover the active role of consent, identifying an autonomous regulatory statute and a new form of data belonging, able to guarantee effective protection of the interested parties.
Keywords: Big data; health data; digitalization; data processing; predictive medicine